2021
DOI: 10.21037/atm-21-2737
|View full text |Cite
|
Sign up to set email alerts
|

Role of competitive endogenous RNA networks in the pathogenesis of coronary artery disease

Abstract: Background: The present study aimed to construct a network of competitive endogenous RNAs (ceRNAs) related to the pathogenesis of coronary artery disease (CAD), to provide a novel rationale for CAD treatment.Methods: Bioinformatics methods were applied to screen for differentially expressed long non-coding RNAs (DElncRNAs), microRNAs (DEmiRNAs), and mRNAs (DEmRNAs) from the GSE68506, GSE59421, and GSE20129 datasets of the Gene Expression Omnibus (GEO) database. The miRcode database was used to predict lncRNA-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Activation of the PI3K/Akt signaling pathway is well known to accelerate the development of atherosclerosis ( 52 ). As suggested by a recently published study ( 53 ), this pathway plays an important role in the pathology of CAD. The affected proteins play functional roles in biological processes of peptidyl-tyrosine modification, innate immune response-activating signal transduction, positive regulation of cell migration, MAPK cascade, blood coagulation and so on.…”
Section: Discussionmentioning
confidence: 78%
“…Activation of the PI3K/Akt signaling pathway is well known to accelerate the development of atherosclerosis ( 52 ). As suggested by a recently published study ( 53 ), this pathway plays an important role in the pathology of CAD. The affected proteins play functional roles in biological processes of peptidyl-tyrosine modification, innate immune response-activating signal transduction, positive regulation of cell migration, MAPK cascade, blood coagulation and so on.…”
Section: Discussionmentioning
confidence: 78%
“…The increase in apoptosis is attributed to a decrease in MDM2 and increase in p53 signal transduction [ 32 ]. Disruption of this regulatory mechanism can lead to excessive cell growth [ 33 ]. Studies demonstrated that MDM2 inhibition can reduce cardiac dysfunction and fibrosis following myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%